Edukasi Pedoman Isi Piringku Pada Anak Sekolah dalam upaya meningkatkan Pengetahuan Gizi Seimbang Pada Siswa Kelas 4, 5 dan 6 di SDN 005 Lubuk Baja Kota Batam - Siska Pratiwi; Haqqelni Nur Rosyidah; Aprilya Roza Werdani; Desy Desy; Lala Atika (Universitas Maritim AMNI Semarang, 2022)
The Ministry of Health introduced the “Fill My Plate” program as a daily food guide to achieve good nutritional status. The concept of the contents of my plate visually shows the composition of the food on one plate for one meal. 50% of the contents of the plate in